A Literary Review on Pumsavana Karma (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is the science of life and it is one of the most ancient healing methodologies in the world. This system is transmitted from immortals to mortals. There are various Samhitas written by our Acharyas related to health of the human beings. Pumsavana karma is one of the most important Samskara mentioned in Ayurveda. It is one of the Shodasha Samskaras performed in various stages of life in ancient India explained by scholars of Ayurveda. It can be done before the conception or immediately after the conception to achieve healthy and desired progeny during Pushya nakshatra. In Ayurveda, Pushya nakshatra is often considered a favourable time for various health related activities. It is believed that beginning Ayurvedic treatments during Pushya nakshatra can enhance their effectiveness and yield better results.  It deals with the technique of genetic engineering and it can be considered to have some action on human genetics to ensure healthy progeny. Moreover, the complexion, glow, mental health of child can be improved through Pumsavana karma. In this article the importance of Pumsavana karma has described that which is not only for desired sex but also to achieve healthy progeny by using different formulations mentioned in various Samhitas was explained.